Price pass-through along the supply chain: Evidence from PPI and CPI microdata - Edvin Ahlander; Mikael Carlsson; Mathias Klein (Sveriges Riksbank, 2023)
We examine the pass-through from producer to consumer prices, using product-group data derived from the microdata underlying the official Swedish PPI and CPI indices. We find a robust pass-through, in line with theoretical models emphasizing production inter-linkages between sectors. The results also display important heterogeneity in pricing behavior both along the supply chain, as well as across product groups. That is, upstream pricing seems much more rigid than downstream pricing in the supply chain and the pass-through across CPI products varies substantially with price-change frequencies. The recent COVID- and high-inflation periods do not change the main results.
Keywords: E30; E31; E32; 330; Price pass-through; consumer and producer prices; microdata